2016
DOI: 10.1590/2317-1782/20162015166
|View full text |Cite
|
Sign up to set email alerts
|

Valores de nasalância para sílabas produzidas por falantes do Português Brasileiro

Abstract: RESUMO Objetivo o objetivo do estudo foi estabelecer valores de nasalância para sílabas produzidas por falantes do Português Brasileiro com diferentes idades e sexo. Métodos Participaram deste estudo 245 falantes do Português Brasileiro (121 do sexo masculino e 124 do sexo feminino), de ambos os sexos, divididos em quatro grupos de idade: 57 crianças, 61 adolescentes, 65 adultos jovens e 62 adultos. Valores de nasalância foram obtidos para um conjunto de 14 sílabas (dez orais e quatro nasais), utilizando o N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
2
1
0
1
Order By: Relevance
“…Similar results were seen for Hungarian and Korean speaking children (26,27) and for a normal Brazilian Portuguese speaking population, including children, adolescents, young adults and adults (15) . The lower nasalance scores seen in the production of the neutral vowel is related to the position of the tongue (lower) and the size of the oral cavity (larger).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar results were seen for Hungarian and Korean speaking children (26,27) and for a normal Brazilian Portuguese speaking population, including children, adolescents, young adults and adults (15) . The lower nasalance scores seen in the production of the neutral vowel is related to the position of the tongue (lower) and the size of the oral cavity (larger).…”
Section: Discussionsupporting
confidence: 82%
“…The use of nasometry in different countries soon has shown that nasalance varies according to the language spoken (9)(10)(11)(12)(13) . Studies with Brazilian Portuguese speakers, including children, have shown that nasalance can also vary according to age, gender or the type of emission (syllables and/or sentences) (14,15) , confirming observations for other languages (13,(16)(17)(18)(19)(20)(21)(22) .…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…5007/1984-8420.2018v19n1p18 mulheres exibiram maior ênfase e maior tempo na emissão dos sons-alvo em contexto átono (pós-tônico), ou seja, maior duração da consoante nasal em sílaba final, levando a um maior fluxo aéreo nasal nesta posição da palavra do que em sílaba medial. Ainda, esses diferentes resultados entre o sexo masculino e feminino corroboram estudos do PB sobre características aerodinâmicas de sons nasais (MARINO et al, 2016;MENDONÇA;SEARA, 2015). O estudo de Marino et al (2016) Passaremos aos resultados quanto ao contexto de vogal precedente e sua influência nos parâmetros aerodinâmicos aqui investigados.…”
Section: Contexto De Tonicidadeunclassified